2015
DOI: 10.1364/oe.23.013467
|View full text |Cite
|
Sign up to set email alerts
|

Splitting and combining properties of an elegant Hermite-Gaussian correlated Schell-model beam in Kolmogorov and non-Kolmogorov turbulence

Abstract: Elegant Hermite-Gaussian correlated Schell-model (EHGCSM) beam was introduced in theory and generated in experiment just recently [Phys. Rev. A 91, 013823 (2015)]. In this paper, we study the propagation properties of an EHGCSM beam in turbulent atmosphere with the help of the extended Huygens-Fresnel integral. Analytical expressions for the cross-spectral density and the propagation factors of an EHGCSM beam propagating in turbulent atmosphere are derived. The statistical properties, such as the spectral inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…For further investigating the propagation properties of the OCVLs, we also study the M 2 -factor and beam wander [49][50][51]. The beam's second-order moments in turbulent atmosphere in the receiver plane are obtained as follows [51]:…”
Section: Formulation Of the Propagation Of Oclvs In Turbulent Atmospherementioning
confidence: 99%
“…For further investigating the propagation properties of the OCVLs, we also study the M 2 -factor and beam wander [49][50][51]. The beam's second-order moments in turbulent atmosphere in the receiver plane are obtained as follows [51]:…”
Section: Formulation Of the Propagation Of Oclvs In Turbulent Atmospherementioning
confidence: 99%
“…Based on the sufficient condition for devising genuine correlation functions of partially coherent beams proposed by Gori et al [26,27], Chen et al introduced a class of partially coherent beam with a special spatially correlation function named Hermite-Gaussian correlated Schell-model (HGCSM) beam in 2015 [28]. The propagation properties of the HGCSM beam in free space, focusing optical system, Kolmogorov and non-Kolmogorov turbulent atmosphere have been investigated in detail [28][29][30][31]. It was found that the HGCSM beam exhibits many extraordinary properties, such as self-splitting on propagation in free space, splitting and combining in focusing optical system, and turbulent atmosphere, and selfhealing properties when a portion of the spot is obscured.…”
Section: Introductionmentioning
confidence: 99%
“…Various partially coherent beams with prescribed correlation functions have been investigated in both theory and experiment since Gori and collaborators derived the sufficient condition for constructing the genuine correlation functions [2,3] . Recent studies have shown that specially correlated partially coherent beams display many unique but interesting properties, e.g., self-splitting effect appears in a Hermite-Gaussian correlated Schellmodel beam on propagation [9][10][11] , partially coherent beams with multi-Gaussian, Bessel-Gaussian and cosine-Gaussian correlated Schell-model functions exhibit prescribed farfield intensity distributions [12][13][14][15] , Laguerre-Gaussian correlated Schell-model beam produces an optical cage near the focal plane [16,17] . Due to those extraordinary properties, specially correlated partially coherent beams are useful in some applications, such as optical imaging, particle trapping, atom guiding and free-space optical communications.…”
Section: Introductionmentioning
confidence: 99%